2022
DOI: 10.1021/acs.jpca.2c04538
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Theoretical Investigation of Reactions of Formyl (HCO) Radicals in the Gas Phase: (I) Kinetics of HCO Radicals with Ethyl Formate and Ethyl Acetate in Tropospherically Relevant Conditions

Abstract: Formyl (HCO) radicals were generated in situ in the gas phase via the photolysis of glyoxal in N2 at 248 nm using the pulsed laser photolysis–cavity ring-down spectrometry technique, and the absorption cross-section of the radical was measured to be σHCO = (5.3 ± 0.9) × 10–19 cm2 molecule–1 at 298 K and 615.75 nm, which was the probing wavelength. The kinetics of the reactions of HCO radicals with ethyl formate (EF) and ethyl acetate (EA) were investigated experimentally in the temperature range of 260–360 (±2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Initiation of the VOC oxidation process is primarily driven by the sunlight-derived OH radical but also via reactions involving other oxidants. Papers in this virtual special issue include studies of the initiation reactions of VOC species by OH, Cl, O 3 , , NO 3 , and HCO, as well as by direct photolysis . Chamber studies, in which the products of a VOC oxidation process are identified and quantified, are also prevalent; two studies quantify the formation of secondary organic aerosol (SOA) in the reaction of OH or NO 3 with monoterpenes, , while a combined experimental/theoretical study shows that methylmethanimine oxidation via the OH radical is unlikely to compete with atmospheric hydrolysis of this species .…”
mentioning
confidence: 99%
“…Initiation of the VOC oxidation process is primarily driven by the sunlight-derived OH radical but also via reactions involving other oxidants. Papers in this virtual special issue include studies of the initiation reactions of VOC species by OH, Cl, O 3 , , NO 3 , and HCO, as well as by direct photolysis . Chamber studies, in which the products of a VOC oxidation process are identified and quantified, are also prevalent; two studies quantify the formation of secondary organic aerosol (SOA) in the reaction of OH or NO 3 with monoterpenes, , while a combined experimental/theoretical study shows that methylmethanimine oxidation via the OH radical is unlikely to compete with atmospheric hydrolysis of this species .…”
mentioning
confidence: 99%